ANALISIS PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK - Winarti Monika Sagala; Dwi Ratmono (Diponegoro Journal of Accounting, 2015)
The aim of this study is to examine the effect of disclosure of Corporate Social Responsibility (CSR) to corporate tax aggressiveness. The independent variable is used in this study is corporate social responsibility disclosure.While the dependent variable in this study is tax aggressiveness that measured using proxy Effective Tax Rates (ETR). This study is a replication of the study by Lanis and Richardson (2012) and use 375 non-financial companies that listed on the Indonesia Stock Exchange in the period 2011-2013 as the sample. Samples were selected by probability sampling method and finally obtained 125 non-financial companies that fulfill the criterias. Data were analyzed using ordinary least square regression analysis model.The result shows that the higher the level of CSR disclosure of a corporation, the lower is the level of tax aggressiveness. This result support the theory of legitimacy.